Chronic Kidney Disease: A Public Health Problem That Needs a Public Health Action Plan - Anton C. Schoolwerth, MD, MSHA; Michael M. Engelgau, MD; Thomas H. Hostetter, MD; Kathy H. Rufo, MPH; Dolph Chianchiano, JD, MPA; William M. McClellan, MD, MPH; David G. Warnock, MD; Frank Vinicor, MD (Centers for Disease Control and Prevention, 2006)
For a health problem or condition to be considered a public health issue, four criteria must be met: 1) the health condition must place a large burden on society, a burden that is getting larger despite existing control efforts; 2) the burden must be distributed unfairly (i.e., certain segments of the population are unequally affected); 3) there must be evidence that upstream preventive strategies could substantially reduce the burden of the condition; and 4) such preventive strategies are not yet in place. Chronic kidney disease meets these criteria for a public health issue. Therefore, as a complement to clinical approaches to controlling it, a broad and coordinated public health approach will be necessary to meet the burgeoning health, economic, and societal challenges of chronic kidney disease.